Delegation of Authority From The General Court to the Shariah Court in Nanggroe Aceh Darussalam Province - Alsyam; Yandriza; Zulkifli (Ekasakti Journal of Law and Justice, 2025)
Law enforcement carried out by the Aceh Syar'iyah Court cannot be separated from the bureaucracy which is one of the vehicles in the implementation of judicial power. Bureaucracy is a determining factor in the success of the entire program agenda including in the framework of realizing a clean and free judicial apparatus from KKN so that the bureaucrats in the Aceh Syar'iyah Court can realize good governance (good governance). The Aceh Syar'iyah Court in carrying out all activities related to the interests of the Appellate Court, both administrative, financial and organizational in nature, is obliged to be accountable for the implementation of its duties, functions and roles in the management of resources, and sources of funds and authorities entrusted to the public referring to the Decree of the Secretary of the Supreme Court of the Republic of Indonesia Number: MA / SEK / 07 / SK / III / 2006 concerning the Organization and Work Procedures of the Secretariat of the Supreme Court of the Republic of Indonesia, the Supreme Court of the Republic of Indonesia as one of the state / government institutions in accordance with the Decree of the People's Consultative Assembly Number: XI / MPR / 1998 concerning the Implementation of a Clean and Corruption-Free State, Collusion and Nepotism and Presidential Instruction Number: 7 of 1999 concerning Accountability of Government Agency Performance. The legal research method is a systematic way of conducting research. Normative legal research uses normative case studies in the form of legal behavior products, for example reviewing laws. The results of this study explain that first, the Syar'iyah Court only carry out its functions within the scope of the authority of the Religious Court in the field of marriage, inheritance, will, grant, waqaf, zakat, infaq, sadaqah and sharia economy, whereas criminal matters are only limited to matters alcohol(liquor), solitude (pervert),gambling(gambling). Second, the authority of the Sharia Court is no longer limited to certain civil matters, but also covers the fields of mu'amalah and jinayah. However, in fact, the laws and regulations concerning the duties of the Sharia Court are still incomplete and thisThis is one of the problems faced. While Law Number 48 of 2009 no longer explains about the Syar'iyah Court until the position and the authority of the Sharia Court in Aceh becomes unclear